The dissemination of science in Angola through scientific journals: an alternative of improving the research process - Wongo Gungula, Eurico; Artigas, Wileidys; Faustino, Arnaldo (Revista General de Información y Documentación, 2020)
The interest that the international scientific community attributes in the training of the new generation of professionals for scientific research is indisputable and positive. Angola, being a country marked by various civil conflicts; in recent years, it has been interested in training researchers to advance university education and position the country in various international rankings. In this sense, some institutions have managed to create scientific journals, which leads to training in various investigative processes for in their teaching staff. The objective of the article is to examine the Angolan journals that are registered in the international ISSN portal and their current situation as an alternative to improve the institutions' investigative process. For this, a review was made on the international ISSN portal to identify the journals registered and linked to Angolan institutions. Subsequently, a review of these was carried out on their web pages, as well as the institutions that edit them as a complement to the process. The results achieved indicate that the intention in the creation of scientific journals exists, however, there is insufficient encouragement on the part of the institutions in charge of improving the science indicators of Angola, and with this, achieve the positioning of their journals in the international scenary.
Keywords: Scientific Research; Scientific Journals; Dissemination of Science; Research Process; Angola